IMPLIKASI PENERAPAN PERMENPAN RB NO.6 TH 2014 PADA PERAN HUMAS PEMERINTAH PROVINSI BANGKA BELITUNG - Rahmadini Rosalia (MEDIAKOM : Jurnal Ilmu Komunikasi, 2018)
This research uses interpretative paradigm with qualitative method through data collection techniques in the form of in-depth interviews. The discussed phenomenon through qualitative descriptive frames were public relations practices that occurred in Bangka Belitung Province government by targeting public relations expert-level institutions, and skilled level institutions of public relations as a research subject that was reinforced with department heads and the assessment team as professionals are considered able to provide an assessment of the role of institutions of public relations aim to strengthen and obtain the deep of data. Total respondents were 38 people selected through purposive sampling with details social institution 20 people and experts as many as 9 people, added by 4 heads of agencies that were superior institution of public relations, as well as 5 people who assessed the dupak directly. The results showed that the public relations practices in Bangka Belitung were measured through categorization namely the understanding of public relation practitioners to define the public relations and its duties, the position and role of public relations practitioners in each agency, vertical and horizontal responses accepted by public relations practitioners in agencies, and the communication model in the scope of the Provincial Government of Bangka Belitung has not ideal yet. The public relations practice that refers to the Permenpan-RB standard cannot yet be maximally implemented because it is constrained by many factors including the superior policy factor. Meanwhile the implications of the implementation of Permenpan-RB are the facilities of public relations in carrying out their duties because the Permenpan is the reference standard. The public relations tasks are also directed, focused and planned. Permenpan-RB is also a legal basis for Bangka Belitung’s public relations in their steps. Keywords : Public relations roles, technical roles, government managers, public relations, Broom and Dozier